Santa Dica ou Reduto dos Anjos: uma visão psico-social - Silva, Jeane das Graças Araujo (2005)
This dissertation has as object the studying of Saint Dica`s case, occurred in Lagoa Village, nowadays Lagolândia, district of Pirenópolis, in Goiás State, in the second decade of 20th century. Analyzed by others researchers was interpreted as being a social movement of messianic kind, common, at the beginning of the Republic, as Muckers, Canudos, Contestado, Juazeiro had happened. The main objective of the refered work is try to explain this kind of movement as being created by archetype of Terra Sem Mal, present in the Brazilian imaginary, that showed up in political, economic social crises situations. The principal hypothesis was settled with: if it is possible to understand profoundly these social movements named milenaristas, as being myths that belong to the humanity imaginary. The studies of Jung are usuful as basis to the discussion about archetypes, the ones of Sergio Buarque de Holanda are based in the vision of the paradise of colonizing that stood in the imaginary of the Brazilian people. The sense of this utopia of paradise was interpreted by the symbolic study of Eliade and complemented with the Eternal Return of the same phenomenologist. To the history part of the chosen subject the author exploited the dissertation of professor Lauro Vasconcelos, the first academic informative about Saint Dica and also with the dissertation of professor Eleonora Zicari. Newspapers, magazines, movie documentaries and field researches, complemented the data collectio Hermeneuticas being the search of sense of the social actor behavior served to reveal Saint Dica movement. The most important conclusion of this dissertation is that, albeit the political, economic and social crises, and even the ones psychologics may contribute to the rising of these movements, however, there is, independent of these external conditions, in the human imaginary, an appeal to the Paradise. In the imaginary of the Brazilian people this archetype has a cultural historical support, since the arrival of the Portuguese going through the republic messianic movement, and this appeal, as Eliade says, acts in a circular way, that is, goes and comes back, it is a Myth that always returns, specially in Saint Dica case, still present, in Lagolândia, in spite of her leader had died in 1970, thirty years ago.